Intelligence Factors In Early Children In Primary Schools (SD) 066 Soposorik Panyabungan Utara - Aisyah Siregar, Ummi; Nasution, Khairunnisa (Jurnal Hata Poda, 2025)
Early childhood education is a very important initial stage in building a child's potential and character as a whole. At this age, intelligence development becomes the main factor that influences their success in the learning process and social interactions later in life. Therefore, understanding the factors that influence the intelligence of early childhood is very important so that the learning process can run optimally and in accordance with their development. This research aims to identify factors that influence the intelligence of early childhood at Elementary School (SD) 066 Soposorik Panyabungan Utara. The methodology used is a qualitative approach using observation, in-depth interviews and documentation studies of students, teachers and parents. The research results show that family environmental factors, the role of teachers, and access to learning facilities contribute significantly to the development of children's intelligence. These findings emphasize the importance of collaboration between families and schools in supporting the optimization of early childhood intelligence potential.  Key words: intelligence, early childhood, environment.